An Esterase‐Sensitive Prodrug Approach for Controllable Delivery of Persulfide Species. (16th August 2017) - Zheng, Yueqin; Yu, Bingchen; Li, Zhen; Yuan, Zhengnan; Organ, Chelsea L.; Trivedi, Rishi K.; Wang, Siming; Lefer, David J.; Wang, Binghe
Abstract: A strategy to deliver a well‐defined persulfide species in a biological medium is described. Under near physiological conditions, the persulfide prodrug can be activated by an esterase to generate a "hydroxymethyl persulfide" intermediate, which rapidly collapses to form a defined persulfide. Such persulfide prodrugs can be used either as chemical tools to study persulfide chemistry and biology or for future development as H2 S‐based therapeutic reagents. Using the persulfide prodrugs developed in this study, the reactivity between S ‐methyl methanethiosulfonate (MMTS) with persulfide was unambiguously demonstrated. Furthermore, a representative prodrug exhibited potent cardioprotective effects in a murine model of myocardial ischemia‐reperfusion (MI/R) injury with a bell shape therapeutic profile.